Contemporary Skull Base Surgery A Comprehensive Guide to Functional Preservation - Youssef, A. Samy.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This text is designed to function as a comprehensive guide/companion that will not only facilitate the decision-making process for the surgeon, but also help young surgeons build a successful career in skull base surgery. It is divided into six main sections: The first section details the general principles that every skull base surgeon needs to be acquainted with - skull base anatomy, developing a multidisciplinary skull base team, operating room equipment, surgical instruments, and modern imaging technologies. These are the key elements that play a major role in optimizing functional outcomes and patients$1 (Bquality of life. Following this, the compartmental anatomy chapters set the stage for understanding the technical and surgical nuances of each location. The subsequent five sections are organized as anatomical compartments or regions of the skull base. Every region is organized in the same format for uniformity and ease of use. Each section includes the available treatment choices to each compartment, and describes the relevant pathologies. The contribution of worldwide leaders including neurosurgeons and otolaryngologists provides top-level expertise in how to tackle each pathology. The surgical approaches chapters that lead each anatomical section describe operative techniques in a clear. stepwise fashion with accompanying intra-operative photos and surgical videos. In the individual pathology chapters, different pathological subtypes are described with representative radiographic images of clinical case examples. Accompanying each pathology is a treatment algorithm based on tumor morphology, pre-operative clinical status, and the goal of maximum functional preservation with a brief description of surgical approaches. This will serve as a roadmap that will help the reader to easily reach a decision of how to treat each skull base pathology. The general theme is functional and anatomical preservation of key neurovascular structures. Setting such structures as a target and planning an approach that minimizes iatrogenic damage to these structures will lead the surgeon down the road of either open, endoscopic, or a combination of both approaches. A comprehensive book that is versatile to serve as a handbook as well as a detailed reference for skull base surgery does not currently exist. In addition, combining the two main surgical schools represented by endoscopy and open surgery into one reference enhanced by treatment algorithms is another unique feature. .s
Evolution of the Multidisciplinary Skull Base Team -- Surgical Anatomy of Cranial Nerves -- Compartmental Anatomy: Microsurgical and Endoscopic -- The Operating Room -- Surgical Positioning -- Cranial Nerve Functional Preservation: Tricks of the Trade -- Neurophysiologic Monitoring -- Microdissection Tools -- Neuroimaging Precision Tools -- Skull Base Reconstruction -- Role of Radiotherapy in Modern Skull Base Surgery -- Cerebral Revascularization -- Cranial Nerve Repair and Rehabilitation -- Open Surgical Approaches -- Endoscopic Endonasal Approaches -- Keyhole Approaches -- Meningioma -- Craniopharyngioma -- Pituitary Adenoma -- Sinonasal Cancer -- Surgical Approaches: Open and Endoscopic -- Meningioma -- Pituitary Adenoma -- Schwannoma -- Chordoma and Chondrosarcoma -- Open Surgical Approaches -- Endoscopic Endonasal Approaches -- Trigeminal Schwannoma -- Middle fossa Approach for Hearing Preservation -- Expanded Middle Fossa Approach: Anterior Petrosectomy -- Pretemporal Transcavernous Approach -- Endoscopic Endonasal Transcavernous Approach -- Open Surgical Approaches -- Endoscopic Endonasal Transpterygoid Approaches -- Keyhole Approaches -- Petroclival Meningioma -- Vestibular Schwannoma -- Cerebellopontine Angle Epidermoid Tumor -- Chordoma and Chondrosarcoma -- Pineal Tumors -- Open Surgical Approaches -- Endoscopic Endonasal Approaches -- Meningioma -- Schwannoma -- Paraganglioma -- Chondrosarcoma -- Open Approaches -- Endoscopic Endonasal Approaches -- Paraganglioma -- Juvenile nasopharyngeal Angiomas -- Schwannoma.
Keywords: Nervous system -- Surgery; Neurosurgery; Skull Base -- surgery; Neurosurgical Procedures -- methods